Efeitos da política de avaliação do PDE no sistema municipal de ensino - Vasconcelos, Ana Claudia Celice Alves [UNESP] (2014)
This research has analyzed, mainly, the effects of assessment policy on large scale of basic education, implemented from the creation of the Plan of Educational Development (PDE) in 2007, in the management of the municipal schools of Araçatuba, a city upstate São Paulo, and of municipal schools. As analytical referential, fundamentally, the policy cycle approach, by Stephen J. Ball, has been used, besides bibliographic research. The data regarding the municipal education management and the schools has been raised from the access to the Education Ministry specific computational systems and the analysis of documents. The research has presented the profile of assessment policies in the context of the educational reforms, after the 1950 decade, considering the modifications in the State, the relations with the market and with the process of policies internationalization. Examined, also, the assessment policies of the 1990's, in the area of Brazilian Federal State's administrative reforms. The research did the survey of historical, political and conceptual elements of PDE, and the official actions that focus directly in school, such as the PDE Escola (School PDE) and the Basic Education Quality Indicators (IDEB). It analyzed the Araçatuba's specific case, which concerns to the effects of these policies in the management of the educational system and the municipal schools, and the dimensions and implications of assessment policies in large scale in the process of policies production of the municipal education management. Ultimately, the research results pointed that the actual large scale assessment policy to the basic education, from the implementation of IDEB, produces divergent effects in the local educational management and in the analyzed schools, depending on the established policy, be the ones coming out of actions of the local education system itself, like the process of municipal assessment, or the ones protagonized by the Federal...